School Dropout in Italy: A Secondary Analysis on Statistical Sources Starting from Primary School - Rosa Vegliante; Alfonso Pellecchia; Sergio Miranda; Antonio Marzano (MDPI AG, 2024)
This work reports and discusses the results of a secondary analysis on statistical data regarding the phenomenon of school dropout in Italy starting from primary school. The research was conducted as part of Next GenerationEU funded by the European Union. The aim is to highlight any territorial differences in the phenomenon at the European, national, and local level. The data were collected from reliable sources (Eurostat, National Institute of Statistics, Ministry of Education and Merit, Regional School Office of Campania) and are updated to the latest year available. In line with the goals of PRIN, the aim was to photograph the national situation starting from the results of the INVALSI tests recorded in primary and lower secondary schools. The results of the analysis show that the levels of school dropout in Italy are among the highest in EU countries and, within our country, the well-known gap between the North and South remains, with the latter in a worse position. An econometric model is presented that demonstrates a cause-effect relationship that goes from the results of the primary cycle to those of the secondary cycle. This outcome attests to the importance of strengthening and increasing the skills necessary to prevent the possible conditions of school dropout starting from primary school.